INTEGRATED LICENSING INFORMATION SYSTEM (SIJITU) APPLICATION IN LICENSING SERVICE (A Study at Department of Capital Investment and One-Stop Integrated Services in Ponorogo District) - Lely Indah Mindarti; Nurjati Widodo; Mohammad Putra Surya Mahendra (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
SIJITU (Integrated Licensing Information System) is an application developed by Department of Capital Investment and One-Stop Integrated Services (DPMPTSP) in Ponorogo District in order to provide effective, efficient, and transparent service in Non-Business Licensing Service. The reason behind SIJITU application is the rise of management information system so it can be utilized in the process of licensing service implementation at DPMPTSP in Ponorogo District. This research aims to identify, analyze, and describe SIJITU implementation in Non-Business Licensing Service at DPMPTSP in Ponorogo District that includes implementation strategy, resources involved, procedure and mechanism, and service improvement through SIJITU. This research is a descriptive research with qualitative approach. The method of data analysis used is data analysis of Miles, Huberman, and Saldana’s interactive model that involves data collection, data condensation, data presentation, and conclusion verification or description. The result of the research is that SIJITU application certainly helps the performance of public service in non-business license field that is held by DPMPTSP in Ponorogo District. Through SIJITU application, the service process can be done transparently with the tracking feature. DPMPTSP in Ponorogo District also tries to increase the officers’ ability through formal and non-formal education, and conducts socialization to the society regarding SIJITU application. Services procedure and mechanism through SIJITU can be known in details on the Standard Operating Procedure (SOP) of Licensing Service at DPMPTSP in Ponorogo District